Multi-directional plasmonic surface-wave splitters with full bandwidth isolation - Gao, Zhen (2016)
We present a multidirectional plasmonic surface-wave splitter with full bandwidth isolation experimentally based on coupled defectsurface modes in a surface-wave photonic crystal. In contrast to conventional plasmonic surface-wave frequency splitters with polaritonic dispersion relations that overlap at low frequencies, this multidirectional plasmonic surface-wave splitter based on coupled defectsurface modes can split different frequency bands into different waveguide branches without bandwidth overlap. Transmission spectra and near-field imaging measurements have been implemented in the microwave frequencies to verify the performance of the multidirectional plasmonic surface-wave splitter. This surface wavestructure can be used as a plasmonic wavelength-division multiplexer that may find potential applications in the surface-wave integrated circuits from microwave to terahertz frequencies.